FERMENTED BUFFALO MILK (DADIH) POWDER AS PARABIOTICS WITH LOWERED WATER ACTIVITY TO PROTECT OXIDATIVE STRESS AND LIVER INJURY - Marliyati, Sri Anna; Saufani, Iza Ayu; Palupi, Eny; Handharyani, Ekowati (Food and Feed Research, 2026)
Dadih powder is dried fermented buffalo milk. This study evaluated the effectiveness of dadih powder enriched with modified cassava flour (MOCAF) on metabolic syndrome parameters in Sprague-Dawley rats. Formulations containing 10, 30, and 50% MOCAF were assessed for physicochemical properties and lactic acid bacteria (LAB) viability. The optimal formulation was determined using the deGarmo method, based on the proximate composition and total LAB, and identified the 10% MOCAF formulation as having the highest effectiveness score. This formulation was used in the intervention study. The rats were divided into four groups: normal diet (N), high-fat-high-sucrose diet (KN), and two treatment groups receiving dadih powder supplementation at 0.335 mg/g (D1) and 0.670 mg/g (D2) of body weight for eight weeks. The rats were then sacrificed, and blood and liver samples were collected for biochemical and histological analyses. Traditionally, fresh dadih is highly perishable, with a shelf life of approximately three days. Drying reduced the water activity from 0.70 to 0.66, thereby enhancing stability and prolonging its shelf life. The drying process effectively maintained the viability of LAB at level up to 102 cfu/g, thereby allowing the product to be classified as parabiotic. Dadih powder supplementation significantly reduced malondialdehyde levels, indicating antioxidative activity, although the reductions in glucose and lipid profiles were not significant. Histopathological analysis revealed severe hepatic steatosis in the KN group, whereas the D2 group exhibited near-normal liver structure. These findings indicate that dadih powder may serve as a parabiotic food to protect against oxidative stress and liver damage associated with metabolic syndrome.